Borrowed Body. - Mason-John, Valerie (Demeter Press, 2013)
""I could have been born and raised in Africa. But my Spirit was in too much of a rush to be reincarnated ... At six weeks I was chucked out into the new year of 1965 which wasn't prepared to welcome on African baby, abandoned on a harsh English winter's day."" So begins Pauline's spirited and moving story of her childhood and teenage years in and out of foster homes and back and forth to Dr. Barnardo's Village in Essex. Her Barnardo's family was ruled by an unlikely trio--Aunty Claire, a fervent Christian; her laconic husband, the German Jewish Uncle Boris; and Aunty Morag, the cook. And, of co.